Pengaruh Penggunaan Tepung Biji Kelor (Moringa oleifera) Terhadap Kualitas Kimia Air Tambak Budidaya - Mulyawan, Ardi Eko (SIGANUS: Journal of Fisheries and Marine Science, 2020)
ABSTRACT: The present study aims to determine the effect of Moringa oleifera seed flour on the chemical paramater of water quality in fish pond. The results of this study are expected to provide information on the use of moringa seed flour on the chemical parameter of water quality of aquaculture. This research was conducted from April to May 2018. A completely randomized design was applied for experimental design. The treatments tested were moringa seed flour consisted of 4 treatments (0 mg/l control, 250 mg / l, 350 mg/l and 450 mg/l) in 2 ponds with different locations, where each treatment had 3 replicates to obtain 24 units trial. The sampling technique used random sampling. The research variables consisted of nitrate, ammonia and phosphate. One way ANOVA was performed for statistical analysis. The results showed that the lowest range of ammonia in pond water was obtained in treatment (450 mg/l) followed by treatment (350 mg/l) and treatment (250 mg/l), while the range of nitrate in pond water, where in pond 1 the lowest nitrate was obtained at treatment (450 mg/l), followed by 350 mg/l and 250 mg/l treatment. In pond 2 the lowest nitrate range was obtained in treatment (250 mg/l) followed by treatment (450 mg/l) and treatment (350 mg/l) ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan tepung biji kelor (Moringa oleifera) terhadap kualitas kimia air tambak budidaya. Hasil dari penelitian ini diharapkan dapat memberikan informasi pemanfaatan tepung biji kelor terhadap kualitas kimia air tambak budidaya. Penelitian ini dilaksanakan pada bulan April sampai Mei 2018. Peneltian ini tergolong dalam penelitian yang menggunakan Rancangan Acak Lengkap (RAL). Perlakuan yang diujicobakan adalah tepung biji kelor dengan 4 perlakuan (0 mg/l kontrol, 250 mg/l, 350 mg/l dan 450 mg/l) di 2 tambak dengan lokasi yang berbeda, dimana setiap perlakuan diulang 3 kali sehingga diperoleh 24 unit percobaan. Teknik sampling menggunakan random sampling. Variabel penelitian terdiri dari nitrat, amoniak dan phospat yang dianalisa dengan menggunakan one way ANOVA. Hasil peneltian menunjukkan kisaran amoniak pada air tambak terendah diperoleh pada perlakuan (450 mg/l) disusul perlakuan (350 mg/l) dan perlakuan (250 mg/l), sedangakan kisaran nitrat air tambak, dimana pada tambak 1 kisaran nitrat terendah diperoleh pada perlakuan (450 mg/l), disusul perlakuan (350 mg/l) dan perlakuan (250 mg/l). Pada tambak 2 kisaran nitrat terendah diperoleh pada perlakuan (250 mg/l) disusul perlakuan (450 mg/l) dan perlakuan (350 mg/l)